The Origin of Congenital Heart Defects and the Basics of Modern Clinical Diagnosis - Yusupov Ziyodulla; Lutfullin Said; Raxmatillayev Rabbonjon (Journal of Science in Medicine and Life, 2025)
Congenital heart defects are a general name for various defects in the structure of the heart and large vessels that form in a child before birth. Because of them, the heart does not function properly and blood flow in the body is impaired. This can lead to serious complications, including death. Congenital heart defects are pathological changes in the structure of the heart chambers, valves, and large vessels that lead to organ dysfunction. They are formed in the womb at 4-6 weeks of embryonic development. They can be caused by chromosomal and gene mutations, as well as the mother's lifestyle and diseases encountered during pregnancy.